ENSURING THE QUALITY OF UNIVERSITY EDUCATION IN CONDITIONS OF BLENDED AND DISTANCE LEARNING - Svitlana Martynenko (Borys Grinchenko Kyiv Metropolitan University, 2020)
In modern conditions of reforming the system of higher education, the introduction of time-based blended and distance learning, the mission of higher education is to ensure the efficiency and quality of university education. Therefore, the problem of using blended and distance learning technologies becomes relevant, which, taking into account the peculiarities of the conduct, should ensure the quality of educational services for students. Blended learning is defined as a hybrid of traditional face-to-face and online learning so that instruction occurs both in the classroom and online, and where the online component becomes a natural extension of traditional classroom learning. The article highlights the peculiarities of the introduction of mixed and distance learning at the university, analyzes and clarifies the essence and content of the concepts of « blended learning», «distance learning», identifies the main approaches, methodical principles underlying the organization of the educational process, the priority tasks and advantages of the introduced forms of education are singled out, the tendencies of their development are outlined, in particular in modern conditions. The methods, organizational forms and means used during blended and distance learning are described, specific examples of their introduction at Kyiv International University are given, as well as the schematic structure of the methodical system of the proposed forms of education that ensure the quality of university education. It is proved that blended and distance learning solves the problems of individualization, intensification and optimization of education, is the most effective evolution of the traditional model of learning.